2014
DOI: 10.1124/dmd.114.058545
|View full text |Cite
|
Sign up to set email alerts
|

Brain Penetration of WEB 2086 (Apafant) and Dantrolene in Mdr1a (P-Glycoprotein) and Bcrp Knockout Rats

Abstract: Transporter gene knockout rat models are attracting increasing interest for mechanistic studies of new drugs as transporter substrates or inhibitors in vivo. However, limited data are available on the functional validity of such models at the blood-brain barrier. Therefore, the present study evaluated Mdr1a [P-glycoprotein (P-gp)], Bcrp, and combined Mdr1a/Bcrp knockout rat strains for the influence of P-gp and breast cancer resistance protein (BCRP) transport proteins on brain penetration of the selective tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
3
16
1
Order By: Relevance
“…It was previously reported that dantrolene brain exposure increased 3-and 6-fold in Abcg2(À/À) mice following an IV bolus dose or IV infusion, respectively (Enokizono et al, 2008;Xiao et al, 2012). In the Abcg2(À/À) rats, C b /C p of dantrolene increased 2-fold in our study and 3-fold in the study recently reported by Fuchs et al (2014). This small difference in dantrolene brain exposure observed between rats and mice was probably due to experimental variations.…”
Section: Animalssupporting
confidence: 70%
“…It was previously reported that dantrolene brain exposure increased 3-and 6-fold in Abcg2(À/À) mice following an IV bolus dose or IV infusion, respectively (Enokizono et al, 2008;Xiao et al, 2012). In the Abcg2(À/À) rats, C b /C p of dantrolene increased 2-fold in our study and 3-fold in the study recently reported by Fuchs et al (2014). This small difference in dantrolene brain exposure observed between rats and mice was probably due to experimental variations.…”
Section: Animalssupporting
confidence: 70%
“…). It was confirmed that ZSQ (1 μM) and FTC (1 μM) are selective P‐gp and BCRP inhibitors, respectively, and MK‐571 (50 μM) is a nonselective inhibitor of P‐gp and BCRP . Using these three chemical inhibitors, the contribution of P‐gp, BCRP, and other transporters that potentially could be inhibited by MK‐571 was evaluated.…”
Section: Resultsmentioning
confidence: 91%
“…34 Given the very low aqueous solubility of PRCBs, their relative lack of BBB permeability suggests that they may be substrates for active drug efflux transporters such as P-glycoprotein or multidrug resistance proteins. Future studies using selective inhibitors of such transporters (e.g., ref 35) or transporter knockout rodents (e.g., ref 36) should help identify precisely the efflux transporters for which PRCBs serve as substrates.…”
Section: Discussionmentioning
confidence: 99%